Rearrange the following equation to find x in terms of a and b in simplest form (assume that a =/-3b)

the / should be through the = to show a is not equal to -3b

Couldnot find the key for it sorry!

3b(x+3b)=a(a-x)

3bx+9b^2=a^2-ax

(3b-a)x=a^2-9b^2

(3b-a)x=(a-3b)(a+3b)

this is where i get unsure.

I think then it becomes

(a-3b)(a+3b)

- ______________

3b-a

which then becomes

x= -(a+b)

which is x= a-b

Are my workings out right or am I completley of the mark?

Apologies for the way i may have presented my workings out still getting to grips with showing my workings out on a computer